Recent Changes in Peatland Testate Amoeba Functional Traits and Hydrology Within a Replicated Site Network in Northwestern Québec, Canada - Zhang, Hui; Amesbury, Matthew J.; Piilo, Sanna R.; Garneau, Michelle; Gallego-Sala, Angela; Väliranta, Minna M. (Frontiers in Ecology and Evolution, 2020)
Northern peatlands, which are highly heterogeneous ecosystems, are a globally important carbon (C) store. Understanding the drivers and predicting the future trajectory of the peatland C store requires upscaling from cores and sites to regions and continents, alongside a detailed understanding of the mechanisms governing their C sequestration. Studies incorporating replication are therefore important to quantify how peatland heterogeneity may affect upscaling from local-scale dynamics to models. In addition, we need to better understand the processes driving observed variability, but the interplay between plants, microbes and C cycling in peatlands remains poorly understood. One approach to address both issues is to examine replicated microbiological functional traits within a multi-proxy framework to provide an ecosystem-level perspective on ecological and biogeochemical processes. Peatland testate amoebae are a functionally important group of protists that are well suited to such an approach. Analysing testate amoeba functional traits provides an opportunity to examine processes that may affect key peatland ecosystem services, such as C sequestration. Here, we compared four key testate amoeba functional traits (mixotrophy, biovolume, aperture size and aperture position) to C accumulation, hydrological and vegetation changes in 12 post-Little Ice Age peat records. Samples were collected from high-boreal and low-subarctic regions in northwestern Québec, Canada in an experimental design that includes internal and external replication at both site and regional scales. Our results showed that correspondence between C accumulation, hydrology and testate amoeba functional traits varied, but recent changes in mixotrophy and aperture size, which may affect peatland C sequestration potential and microbial food web structure respectively, showed tentative links to recent C accumulation increases. Vegetation, especially Sphagnum abundance was important in promoting mixotrophy and small aperture size in testate amoeba communities. Future impacts of climate change on peatland vegetation will further influence the functional role of testate amoebae on C sequestration through changing mixotrophic testate amoeba abundance.